Educational Leadership in Our Peculiar Institutions: Understandings of Principals in Segregated, White-Staffed Urban Elementary Schools in the United States - Milligan, Tonya M.; Howley, Craig B. (International Journal of Multicultural Education, 2015)
This study explores how 10 principals in mostly-Black U.S. urban elementary schools staffed by mostly-White faculty understood and experienced the manifestations of racial differences. Narrative inquiry with nearly 700 pages of transcript data yielded three themes: (1) gradients of color-conscious leadership, (2) principals as moral agents, and (3) working within a context of fear. Difficult though these stories and challenges are in the U.S., practices and policies elsewhere in the world also produce such situations and experiences, and the dynamics evident in the stories told by these school heads may prove relevant to investigations in other national systems.